Phased array optimizing characteristics in HIFU device - Chen, Qi; Xiong, Bin; Chen, Yazu (Archives of Acoustics, 2003)
For the high intensity focused ultrasound (HIFU) phased array frequency distribution pattern size and amount of the elements may affect the performance and cost of the HIFU device. In this paper an inner holed spherical shell with 96 transducer elements was designed basing on the Ebbini pseudo-inverse matrix and Penns bioheat equation. The phased array has a lower grating-lobe level and a higher intensity gain suitable for deep heating. The experiments with the array usung 16 elements show that the phased array design produces a large dynamic scan scale with least elements and a high heat focus. Keywords: focused ultrasound; phased array; bioheat transfer; optimization.